2015
DOI: 10.4067/s0717-95022015000200054
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular Condyle Repair after Partial Condylectomy in Patients with Active Condylar Hyperplasia

Abstract: SUMMARY:The different aspects of unilateral condylar hyperplasia have been studied and continue to be controversial; nevertheless, treatment based on condylectomy has been established as part of the working protocol. The aim of this investigation was to identify the bone repair observed in surgically treated condyles after 1 year using cone beam computed tomography (CBCT). Nine subjects were included in this study (6 female and 3 male) with an average age of 18.5 years. They had been diagnosed with active unil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
1
5
0
6
Order By: Relevance
“…In CBCT, condyle and glenoid fossa remodeling were evident 3 months after the operation, moreover a round and smooth shape condyle with bone corticalization was present at 1 year and 5 months ( Figure 13). This was consistent with Olate et al 13 who reported that 1 year after partial condylectomy the condyle had a round and clear cortical bone, and they also achieved a stable result. In frontal view CBCT, the affected ramus posterior region and the gonial region exhibited resorption, but the right condyle which was displaced a little laterally 1 month after the operation was slowly repositioned medially at 3 months and at 8 months after the operation (Figure 14).…”
Section: Treatment Resultssupporting
confidence: 91%
“…In CBCT, condyle and glenoid fossa remodeling were evident 3 months after the operation, moreover a round and smooth shape condyle with bone corticalization was present at 1 year and 5 months ( Figure 13). This was consistent with Olate et al 13 who reported that 1 year after partial condylectomy the condyle had a round and clear cortical bone, and they also achieved a stable result. In frontal view CBCT, the affected ramus posterior region and the gonial region exhibited resorption, but the right condyle which was displaced a little laterally 1 month after the operation was slowly repositioned medially at 3 months and at 8 months after the operation (Figure 14).…”
Section: Treatment Resultssupporting
confidence: 91%
“…Esta remodelación se produce con formación de hueso cortical, con distancia máxima de 4,5 mm de la fosa mandibular, similar al efecto de avance mandibular mediado por los AF. Esta respuesta condilar evidencia que la reparación y remodelación condilar un año después de la condilectomía proporcionan una morfología condilar similar a la anatomía normal (23) . En el presente caso, los cambios dentarios obtenidos en el tratamiento con AF fueron: corrección de mordida en tijera y arcos dentales conformados y coordinados.…”
Section: Discussionunclassified
“…La elección de tratamiento mediante condilectomia alta fue debido a que esta es una de las técnicas quirúrgicas que cuentan con mayor soporte en la literatura al eliminar la porción dañada del cóndilo y conservar la funcionalidad del mismo, la osteotomía basal mandibular está indicada por fines estéticos para tratar de recobrar la armonía facial Olate et al (2014) reportaron que aquellos pacientes a los que se les realizo osteotomía condilar se les dio seguimiento de 3 a 24 meses, todo este tiempo los pacientes reportaron ausencia de sintomatología dolorosa, pudiendo llevar a cabo sus actividades diarias, sin mostrar cambios en la asimetría ósea. En el caso que mostramos en el control posoperatorio se evidencio significativa mejoría de la armonía facial, así como ausencia total de sintomatología por lo que proponemos el uso de la osteotomía condilar con el apoyo de fisioterapia para la rehabilitación de la articulación temporomandibular.…”
Section: Discussionunclassified